Avaliação ergonômica da interface humano computador de ambientes virtuais de aprendizagem. - Fernandes, Gildásio Guedes (2008)
The objective of this work is to develop a conceptual model in order to evaluate the human-computer interface (HCI) on a macro level. More specifically, it aims to evaluate the usability and functionality of virtual learning environments (VLE) for distance education (DE). Therefore, the specific objectives are: (1) to evaluate the usability of virtual educational environments used in distance education; (2) to analyze the functionality of educational virtual environments used for distance education; (3) to define appropriate parameters to build a conceptual model for the evaluation of educational virtual environment interfaces for distance education. The usability is originated from cognitive science and at the beginning of the 80’s decade, it started to be related to psychology and ergonomics areas. It includes five attributes which contribute for a good computational interface: easy learning, efficient use, easy memorization, low error levels and subjective satisfaction. On the other side, functionality does not depend only on the interface layer, but also on the program layers and on data base, which are in charge of the experts. The model’s construction was made based on a vast bibliographical review and on the general analysis of different computational environmental interfaces. In order to validate the proposed model, it was applied to three virtual learning environments (VLE): Moodle, Solar and e-ProInfo, using a checklist as a verification list. The first one contained 45 items addressed to education professionals. The second had 60 items applied to computational professionals with experience in distance education, and consequently, with knowledge about the usability principles of computational interfaces. The results show a remarkable advantage of Moodle environment among education professionals and Solar environment among computational professionals experienced in distance education. A clear rejection was observed for e-ProInfo among the two studied segments. Finally, the obtained data infer that, even though the proposed model is adequate to evaluate the VLE, it can be improved in order to be used by any higher education professional with experience on the application of digital technologies.